2023
DOI: 10.3389/fpubh.2023.1037946
|View full text |Cite
|
Sign up to set email alerts
|

Availability and readiness of primary healthcare facilities for the management of non-communicable diseases in different districts of Punjab, Pakistan

Abstract: IntroductionNon-communicable diseases (NCDs) and their effects are rising quickly. NCDs such as cardiovascular illnesses, diabetes, cancer, and chronic lung diseases cause 60% of global deaths; of which, 80% occur in developing countries. In established health systems, primary healthcare handles most of the NCD care.MethodologyThis is a mixed-method study conducted to analyze the health service availability and readiness toward NCDs using the SARA tool. It included 25 basic health units (BHUs) of Punjab, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous small-scale investigations in Afghanistan [29], Bangladesh [30], and Nepal [31] found that health facilities weren't ready to provide CVD-related services. Other LMICs [19][20][21] have found that they are facing similar difficulties. Health facilities' lack of readiness in all three countries may be due to inadequate funding raised through domestic and international channels and a lack of political importance [32] given to combating non-communicable disease.…”
Section: Comparable To Other Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous small-scale investigations in Afghanistan [29], Bangladesh [30], and Nepal [31] found that health facilities weren't ready to provide CVD-related services. Other LMICs [19][20][21] have found that they are facing similar difficulties. Health facilities' lack of readiness in all three countries may be due to inadequate funding raised through domestic and international channels and a lack of political importance [32] given to combating non-communicable disease.…”
Section: Comparable To Other Studiesmentioning
confidence: 97%
“…The explanatory variables were chosen based on two criteria: (1) they were available in the SPA survey of the countries under investigation [24-26] and (2) previous research [14,[17][18][19][20][21] had established them as important determinants of readiness of health facilities to provide CVD services. The following variables were considered: facility location, managing authority, facility type, external sources of revenue, quality assurance activities, routine management meetings, external supervision, user fees, presence of trained health provider at facility 24 hours with duty schedule or present on-call, feedback on clients' opinions, health facilities' ability to perform diagnosis and/or treatment, and number of CVD care providers who had received in-service training in cardiovascular disease services during the 24 months before the survey.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the availability of NCD medicines and nutrition products to individual patients remains inadequate in LMICs. This lack of access increases the risk of undermining the effectiveness of healthcare services and hinders progress toward achieving target 3.8 of the Sustainable Development Goals (SDGs), which is related to attaining Universal Health Coverage (UHC) (3,5,6).…”
Section: Introductionmentioning
confidence: 99%